Detection and analysis of symptomatic patterns in audio bio-logical signals at low power consumption and optimized area - Thouheed Ahmed, Syed; Fathima, Mariyam; Tasmiya Tarannum, Syeda; Kiran M. U, Asha (International Journal of Engineering and Technology, 2018)
Audio signal processing for a biometric analysis of a signal is most challenging field in current era. In this paper, a design is proposed for the acquisition of audio signals and then process under a standard pattern values with the consideration of lower attributes such as power and system scalability for detection of symptomatic pattern. In this paper, a subsequent low power design is used with a mathematical matrix with respect to energy, Quasi-Average (QA), and other various coefficients of wavelets under threshold value analysis. In later process of Mel-frequent analysis is processed and distinguished among signals such as cough and sneeze, with most alike patterns for thresholding value of attribute extracted under matching. The proposed system is more feasible with the user inputs and the Indian environment. Typically, this system is designed and dedicated for Indian digital developmentÂ Â